Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de panela granulada en el cantón Archidona, provincia de Napo para el año 2016 - Vera Bermeo, Nelson Vicente (2017)
The present research topic was developed in the province of Napo, Archidona canton, with the main objective of determining the feasibility of implementing a granulated panela production and marketing company in the Canton Archidona of Napo Province In conducting the market study, it was possible to determine that in the Archidona canton there is an effective demand of 268,844 grains of 2 pounds; With an upward current offer of 144,000 cases; Therefore, there is an unsatisfied demand for 117,140 granulated panela for the first year of project life. At the time of the commercialization it has been possible to establish that the product bears the brand called "EL MENJUNJE", with a slogan "Today is a good day to sweeten your life" finishing to achieve a fast positioning in the market offers a 0.05 % Of additional product. Following the financial study, it was established that according to the machinery to be acquired the company will have an installed capacity of 361,944 granulated pans of 2 pounds per year, starting operations with 80% of the capacity indicated, therefore, in the First year will produce 289,555 granulated panela covers. The location of the plant will be in the province of Napo, Archidona canton on the Via San Pablo in the Barrio Lindo, (behind the Educational Unit Leonardo Murialdo). Where will acquire a land of 500m2. In the same way when analyzing the productive process it was established that it takes about 4 hours with 5 minutes. Mentioning in the organizational study it was established that the company EL MENJUNJE will enjoy 5 hierarchical levels: Executives, Executive, Adviser, Auxiliary and Operative, therefore, requires hiring 12 people, creating equal number of sources d work. The company will be incorporated under the legal form of limited liability company, its corporate name is Company producing and marketing granulated panela EL MENJUNJE Cía. Ltda .; The term of duration is 10 years Regarding the financial analysis carried out, the analysis of the investments in fixed assets, deferred assets and working capital required by the project was accepted, indicating that for the operation of the plant it is necessary to invest USD $ 150,335.5; Of this total, 45.10% will be contributed by the partners and the remaining 54.89% will manage a loan at the Financial Institution BanEcuador offering a rate of 9.76% per year. The cost for the first year is USD $ 323,827.70 and the unitary is USD $ 1.60 in the first year including the 30% profit that will be maintained for the 10 years, all this referring to the prices of the competition. Taking into account the estimates made the company will obtain a liquidity benefit of USD $ 55,404.71 for the first year of useful life and the cash flow shows that in this same period the company will have a net flow of USD $ 69,327.00 For the economic evaluation carried out, it shows that it has an estimated break-even point for the first year with the used capacity of 55.46% and in sales USD $ 234,469.42, the project NPV is $ 197,044.15. Meets the goal of increasing and maximizing investment, the IRR is at 21.03% higher than the cost of capital, the Cost Benefit Ratio states that for every dollar invested in the production of granulated panela the company earns USD $ 0.34 cents; Therefore, the capital recovers in the time of 4 years 8 months and 18 days, finally the sensitivity analysis shows that the project supports a 13% increase in its costs. In derivation thanks to the results and analysis obtained during this process it is concluded that the project is feasible technical, organizational, legal, financial and economically.